An unexpected reaction to methodology: an unprecedented approach to transamidation. Issue 110 (14th November 2016) - Rakesh, K. P.; Ramesha, A. B.; Shantharam, C. S.; Mantelingu, K.; Mallesha, N.
Abstract : An unprecedented approach for the synthesis of disubstituted ureas from a cross coupling method using monosubstituted ureas, isocyanates and sodium hydride. Abstract : This report describes an unprecedented protocol for the synthesis of N, N ′-substituted ureas using a cross-coupling method. Mono substituted ureas were modified by an economically viable and simple method using commercially available isocyanates and sodium hydride as the reagents. In addition, the method involves no expensive metal complexes or catalysts and all reactions are carried out at room temperature. Furthermore, both symmetrical and asymmetrical ureas were successfully obtained in single step reactions with reasonable yields.